EGFR and K-Ras Mutations and Resistance of Lung Cancer to IGF-1R Tyrosine Kinase Inhibitors - Kim, Woo-Young (2012)
BACKGROUND: Most patients with non–small cell lung cancer (NSCLC) have responded poorly to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs). We investigated the involvement of insulin-like growth factor 1 receptor (IGF-1R) signaling in primary resistance to EGFR TKIs and the molecular determinants of resistance to IGF-1R TKIs. METHODS: Phosphorylated IGF-1R/insulin receptor (pIGF-1R/IR) was immunohistochemically evaluated in a NSCLC tissue microarray. We analyzed the antitumor effects of an IGF-1R TKI (PQIP or OSI-906), either alone or in combination with a small-molecular inhibitor (PD98059 or U0126) or with siRNA targeting K-Ras or MAPK/extracellular signal-regulated kinase kinase (MEK), in vitro and in vivo in NSCLC cells with variable histologic features and EGFR or K-Ras mutations. RESULTS: pIGF-1R/IR expression in NSCLC specimens was associated with a history of tobacco smoking, squamous cell carcinoma histology, mutant (mut) K-Ras, and wild-type (wt) EGFR, all of which have been strongly associated with poor response to EGFR TKIs. IGF-1R TKIs exhibited significant antitumor activity in NSCLC cells with wt EGFR and wt K-Ras but not in those with mutations in these genes. Introduction of mut K-Ras attenuated the effects of IGF-1R TKIs on NSCLC cells expressing wt K-Ras. Conversely, inactivation of MEK restored sensitivity to IGF-TKIs in cells carrying mut K-Ras. CONCLUSIONS: The mutation status of both EGFR and K-Ras could be predictive markers of response to IGF-1R TKIs. Also, MEK antagonism can abrogate primary resistance of NSCLC cells to IGF-1R TKIs.